Coxiella burnetii (Q‐Fever) Seroprevalence in Prey and Predators in the United Kingdom: Evaluation of Infection in Wild Rodents, Foxes and Domestic Cats Using a Modified ELISA. Issue 6 (31st January 2014) - Meredith, A. L.; Cleaveland, S. C.; Denwood, M. J.; Brown, J. K.; Shaw, D. J.
Summary Coxiella burnetii, the agent of Q‐fever, is recognized as a worldwide zoonosis with a wide host range and potentially complex reservoir systems. Infected ruminants are the main source of infection for humans, but cats and other mammals, including wild rodents, also represent potential sources of infection. There has been a recent upsurge of reported cases in humans, domestic ruminants and wildlife in many parts of the world, and studies have indicated that wild brown rats may act as true reservoirs for C. burnetii and be implicated in outbreaks in livestock and humans. However, investigation of reservoir systems is limited by lack of validated serological tests for wildlife or other non‐target species. In this study, serum samples from 796 wild rodents (180 bank voles, 309 field voles, 307 wood mice) 102 wild foxes and 26 domestic cats from three study areas in the UK were tested for the presence of antibodies to C. burnetii using a commercial indirect ELISA kit modified for use in multiple wildlife species. Test thresholds were determined for each species in the absence of species‐specific reference sera using a bi‐modal latent class mixture model to discriminate between positive from negative results. Based on the thresholds determined, seroprevalence in the wild rodents ranged from 15.6% to 19.1% depending on species (overall 17.3%) and was significantly higher in both foxes (41.2%) and cats (61.5%) than in rodents. This is the first report to quantify seroprevalence to C. burnetii in bank voles, field voles, wood mice, foxes and cats in the UK and provides evidence that predator species could act as indicators for the presence of C. burnetii in rodents. The study demonstrates that wildlife species could be significant reservoirs of infection for both livestock and humans, and the high seroprevalence in domestic cats highlights the potential zoonotic risk from this species.